Pengaruh Modal Usaha, Lokasi Usaha, Lokasi Pemasaran dan Kualitas Produk terhadap Pendapatan UMKM - Andrean Syahputra; Ervina Ervina; Melisa Melisa (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of working capital, business location, marketing location and product quality on MSME income, with loan capital as a moderating variable. This research method is quantitative. This observation was carried out in the Deli Serdang sub-district and used primary data, by conducting a survey using a questionnaire. The data will be tested by, Moderated Regression Analysis (MRA), Absolute Difference Test, Residual Test. The results showed, a) the t value of Business Capital Count -0.066 < 1.976 with a Significant of 0.505> 0.05; b) t value Calculate Business Location 3,564 > 1,976 and sig value = 0.000 < 0.05; c) the value of t Counting Marketing Locations is 2,684 > 1,976 and the value for the significance value is 0,008 > 0,05; d) the value of t Count Product Quality is 0.870 <1.976 while the Amount is at Sig 0.3860 > 0.05; e) The results of the simultaneous test of all variables obtained a calculated F value of 7.866 > F table 2.43 and also a Sig number of 0.000 <0.05. Conclusions, a) business capital does not affect the income of micro, small and medium enterprises and loan capital is not a moderating variable; b) business location affects the income of MSME loans not as a moderating variable; c) marketing location affects the income of micro, small and medium enterprises and loan capital is not a moderating variable; d) product quality does not affect the income of micro, small and medium enterprises and loan capital is not a moderating variable; e) Business Capital, Business Location, Marketing Location and Product Quality Simultaneously influence MSME income. Keywords: Product Quality, Marketing Location, Business Location, Loan Capital, Business Capital, Micro Small Medium Enterprise Income